Studi Moralitas Remaja Keluarga Buruh Pembersih Sarang Walet - Anisah, Giati; Aziz, Su'udin; Rohmawati, Nur (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This study aims to describe the morality of adolescent families of swallow nest cleaning workers with a sub-focus covering adolescent morality problems, factors that cause morality problems, and efforts made by parents to fix adolescent morality problems. This research is phenomenological qualitative research. This research uses data collection techniques of observation, interviews, and documentation. Interviews were conducted on five teenagers who come from families of swallow nest cleaning workers and also five mothers who work as swallow nest cleaning workers. Observations were made on religious activities and children's associations. Based on the results of the study, it was shown that the family youth of swallow nest cleaning workers experienced moral problems, namely being arrogant and arrogant, desperate, unable to control their passions, and angry. While the factors causing the occurrence of morality problems in adolescents include the family environment, friendship, society, mass media, westernization, and the low level of religious education, the efforts made by parents vary in improving adolescent morality, including the methods of advice, punishment, example, habituation. themselves with a disciplined attitude, filtering foreign cultures that enter, instilling religious values ​​, and encouraging children to be involved in community activities such as youth organizations. This is done by mothers to help improve the morality of teenagers.